DESENTRALISASI DAN KAPASITAS KELEMBAGAAN LOKAL DALAM PENINGKATAN KINERJA MANAJEMEN USAHA AYAM BROILER DI KABUPATEN SIDENRENG RAPPANG - Hairuddin Hanafi; Andi Sinrang; Ahmad Mustanir; Andi Nilwana (LPPM Universitas Abdurrab, 2025)
This study aims to analyze the relationship between decentralization of authority and local institutional capacity in improving the performance of broiler chicken farm business management in Sidenreng Rappang Regency. The broiler chicken farming sector is one of the backbones of food security and the local economy, but it still faces challenges in terms of productivity, managerial efficiency, and the implementation of maintenance standards. This research uses a qualitative approach with data collection techniques through observation, in-depth interviews, and documentation of farmers, local government apparatus, and supporting institutions in the livestock sector. The results show that decentralization provides space for local governments to design policies that are responsive to local needs, but the success of its implementation is largely determined by institutional capacity, especially in the aspects of planning, organizing, implementing, and supervising. Local institutions that are adaptive, coordinated, and adequately resourced have proven to be able to drive more efficient and sustainability-oriented management practices. This study recommends strengthening institutional functions through improving human resource competence, targeted budget allocation, and developing a strategic partnership model between the government, farmers, and the private sector. The scientific contribution of this study lies in the integration of the perspectives of public administration and agribusiness management in evaluating the effectiveness of decentralization through local institutional capacity, which can be a conceptual and practical reference in the development of community-based livestock governance.